2019
DOI: 10.1186/s13006-019-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of infant breastfeeding practices in Nepal: a national study

Abstract: Background Optimal breastfeeding practices, reflected by early initiation and feeding of colostrum, avoidance of prelacteal feeds, and continued exclusivity or predominance of breastfeeding, are critical for assuring proper infant nutrition, growth and development. Methods We used data from a nationally representative survey in 21 district sites across the Mountains, Hills and Terai (southern plains) of Nepal in 2013. Determinants of early initiation of breastfeeding, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
55
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 50 publications
13
55
6
1
Order By: Relevance
“…This rate was similar to 67% observed by Karkee et al in central Nepal [21] but more than the national average of 54.9% reported by NDHS 2016 [2]. and 41.8% reported by Bhandari et al [16] Rate of early initiation of breastfeeding varied widely among countries, ranging from 17.7 to 98.4% with a mean of 57.6% [22].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This rate was similar to 67% observed by Karkee et al in central Nepal [21] but more than the national average of 54.9% reported by NDHS 2016 [2]. and 41.8% reported by Bhandari et al [16] Rate of early initiation of breastfeeding varied widely among countries, ranging from 17.7 to 98.4% with a mean of 57.6% [22].…”
Section: Discussionsupporting
confidence: 87%
“…However, the full breastfeeding rate, including predominant breastfeeding, was 51.4% when predominant breastfeeding is added. Bhandari et al reported the rate of predominant breastfeeding, defined as mainly breastfed, not fed solid/ semisolid foods, infant formula, or non-human milk to be 57.2% in Nepal [16]. The global exclusive breastfeeding rate currently stands at 40%, based on data from 129 countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current study includes both urban and rural areas. Again this magnitude was higher than magnitude reported from studies conducted in South Sudan [25], India [26], Nepal [27] which was 53%, 22.4%, 32.7%, respectively. This might stem from differences in cultural beliefs and practices, study setting, health and nutrition policy, and strategies.…”
Section: Discussioncontrasting
confidence: 64%
“…3,9 The introduction of breastfeeding within the first hour of life reduced deaths in Nepal by 19% and in Ghana by 22%. 10,11 Knowing the consequences of delayed initiation of breastfeeding, team approach with small simple measures which will have a high impact with almost nil cost can be achieved with quality improvement initiative. 12 This will also help us practice evidence-based medicine translating research to practical application making bench to bedside practice.…”
Section: Resultsmentioning
confidence: 99%